A Critical Appraisal on Ayurvedaone Swarnaprashana (AYUSHDHARA, 2023)
The administration of processed gold to children is a unique method described in Ayurveda as "Swarnaprashana" by Acharya Kashyapa thousands of years ago. He clearly discussed the administration of Swarna (gold) in children for the benefits of boosting cognition, digestion and metabolism, physical strength, immunity, complexion, fertility, and life span. There are numerous gold formulations and even herbal medications stated by several Acharya for long-term use in children. Swarnaprashana in children is primarily associated with two Ayurvedic contexts: Lehana (supplement) and Jatakarma Samskara (newborn care).This review is an attempt to objectively assess the Ayurvedaone Swarnaprashana with available data. The mode of administration, and advantages prescribed by Susrutha Samhita are covered below, along with information from associated scientific investigations. According to this assessment, the benefits of Swarnaprashana can be obtained on a variety of levels, including as a general health promoter and specifically for improving intelligence, digestion, metabolism, immunity, physical strength, or skin health. For internal administration, Ayurveda recommends only purified and treated gold.